Fermentation-derived Aroma Compounds in Varietal Young Wines from South Africa - Louw, L.; Tredoux, A.G.J.; Van Rensburg, P.; Kidd, M.; Naes, T.; Nieuwoudt, H.H. (South African Journal of Enology and Viticulture, 2016)
The volatile composition of 925 single cultivar young Sauvignon blanc, Chardonnay, Pinotage, Merlot, Shiraz and Cabernet Sauvignon wines of vintages 2005 to 2007, was determined using gas chromatography – flame ionisation detection. Compositional data were compared to published data on young wines from South Africa and other countries. South African young wines analysed in this study had a largely similar volatile composition to that reported in the literature. Significant between-vintage and between-cultivar differences were observed in the volatile composition of the wines investigated in this study. The concentration ranges of four compounds in red wines, hexanol, propanol, diethyl succinate and ethyl lactate, and four compounds in white wines, 2-phenylethanol, hexanoic acid, isoamyl acetate and propanol, were not influenced by vintage effects. This finding was interpreted as the first indication that typical concentration ranges for some aroma compounds can be established for South African young cultivar wines. A trend was observed in the white wines that the alcohols and their respective acetate esters, as well as fatty acids and their ethyl esters, were responsible for the vintage-related effects. Differences in volatile composition between Chardonnay and Sauvignon blanc wines could also largely be explained on the same basis. Classification models were established to discriminate between individual red wine cultivars and between the two white wine cultivars and correct classification rates of respectively, 79 % and 85 % were achieved.